Drought Analysis Using Various Drought Indices in Sub-District Ngemplak - Mulya, Agus Budi; Pudyastuti, Purwanti Sri; Isnugroho, Isnugroho; Budinetro, Hermono (Dinamika Teknik Sipil: Majalah Ilmiah Teknik Sipil, 2024)
The study namely Drought Analysis Using Various Drought Indices in District Ngemplak, Boyolali offers a comprehensive examination of drought phenomena in the Ngemplak, Boyolali district through the lens of various drought indices, aiming to understand the impact on agricultural productivity and propose effective water management strategies. Using data from 2009 to 2023, this study used SPI and PDSI.  Focusing on the Ngemplak, Boyolali district, this research identifies the most relevant drought indices tailored to the local climatic and geographical contexts, analyzes the correlation between these indices and the productivity of primary crops, and suggests sustainable water management practices to mitigate drought risks. The study underscores the importance of adopting a multifaceted and adaptive water management framework, incorporating sophisticated irrigation technologies, and fostering policy reforms to enhance water use efficiency and resilience against climatic variability. It calls for collaborative efforts involving stakeholders across different sectors to implement these recommendations, ensuring the sustainability of water resources and agricultural productivity in the face of drought challenges.